Effect of Suweg Flour (Amorphophallus Campanulatus) on Reducing Blood Glucose Levels in Diabetic Rats - Setyawati, Ika; Rahmasari, Farindira Vesti (Universitas Muhammadiyah Sumatera Utara, 2024)
Suweg (Amorphophallus campanulatus) is a food ingredient with a low glycemic index that contains phenolic and flavonoid antioxidants, as well as glucomannan. Food intake is a key factor in managing Diabetes Mellitus (DM). Diabetes mellitus (DM) is a chronic non-communicable disease that can cause various complications.This study aims to determine the hypoglycemic effect of suweg (Amorphophallus campanulatus) flour. This experimental research used 25 male Wistar white rats divided into five groups. The group is normal (N), positive control (K), standard (S), treatment group with suweg flour 1.25 gr/day(P1), and the treatment group with suweg flour 2.50 gr/day(P2). Data was obtained by measuring glucose levels before and after giving suweg flour. Data were analyzed using paired difference tests (paired sample t-test). This research showsThere was a significant difference in blood glucose levels between the group given suweg flour and the positive control (p0.001). Significant correlation in treatment groups (P1 and P2).It can be concluded that administration of suweg flour (Amorphophallus campanulatus) has hypoglycemic activity (p0.05).Keywords: diabetes mellitus, hypoglycemic, suweg (Amorphallus campanulus)